2022
DOI: 10.1038/s41598-022-21269-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spin-lock times for T1ρ mapping of human knee cartilage with bi- and stretched-exponential models

Abstract: Two optimization criteria based on Cramér-Rao Bounds are compared between each other and with non-optimized schedules for T1ρ mapping using synthetic data, model phantoms, and in-vivo knee cartilage. The curve fitting is done on complex-valued data using an iterative Nonlinear Least Squares (NLS) approach. The optimization criteria are compared based on the Mean Normalized Absolute Error (MNAE) and variance of the estimated parameters. The optimized spin-lock time (TSL) schedules provided improved results over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…While it is known that two T 1ρ ‐weighted images are the minimum necessary for T 1ρ mapping, this study showed that the right choice of the TSLs could improve image quality and parameter estimation, obtaining results better than if three or more nonoptimized TSLs were chosen. The CRLB approach to choosing the TSLs was extended to bi‐exponential and stretched‐exponential T 1ρ mapping, showing that nearly the same quality can be obtained using half of the number of TSLs if they were optimized 70 …”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that two T 1ρ ‐weighted images are the minimum necessary for T 1ρ mapping, this study showed that the right choice of the TSLs could improve image quality and parameter estimation, obtaining results better than if three or more nonoptimized TSLs were chosen. The CRLB approach to choosing the TSLs was extended to bi‐exponential and stretched‐exponential T 1ρ mapping, showing that nearly the same quality can be obtained using half of the number of TSLs if they were optimized 70 …”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
“…The CRLB approach to choosing the TSLs was extended to bi-exponential and stretchedexponential T 1ρ mapping, showing that nearly the same quality can be obtained using half of the number of TSLs if they were optimized. 70 Efficient use of phase-cycling acquisitions in magnetization-prepared angle-modulated partitioned k-space spoiled GRE snapshots (MAPSS) sequences was proposed. 71 To reduce the T 1 contamination that affects the precision of cartilage T 1ρ mapping, MAPSS required essentially two acquisitions with the same TSLs, one regular and the other with phase cycling.…”
Section: Updates On Improved Rf Pulse Sequences and Sequence Optimiza...mentioning
confidence: 99%
“…The 3D‐PETRA‐ T 1 ρ weighted images were acquired with a spin‐lock frequency of 500 Hz and spin‐lock times (TSLs): 0, 0.2, 2.6, 12.9, 12.9, and 30 msec. These TSL values were chosen using previously described optimization experiments 22,23 . Fat suppression and T 1 ρ preparation modules were applied at every 26 readouts to minimize acquisition time.…”
Section: Methodsmentioning
confidence: 99%
“…These TSL values were chosen using previously described optimization experiments. 22,23 Fat suppression and T 1ρ preparation modules were applied at every 26 readouts to minimize acquisition time. The acquisition parameters were as follows: repetition time (TR)/echo time (TE) = 5 msec/0.07 msec, field of view = 200 Â 200 mm 2 , flip angle = 6 , matrix size = 256 Â 256 Â 256, thickness = 0.78 mm, voxel size = 0.78 Â 0.78 Â 0.78 mm 2 , receiver bandwidth = 399 Hz/px, T 1 recovery delay =500 msec, number of radial spokes = 8000, number of segments =350, number of readouts in each segment = 26, and number of Cartesian sample points = 1419.…”
Section: D-t 1ρ -Petra Sequencementioning
confidence: 99%